On-shot laser beam diagnostics for high-power laser facility with phase modulation imaging. (23rd March 2016) - Pan, X; Veetil, S P; Liu, C; Tao, H; Jiang, Y; Lin, Q; Li, X; Zhu, J
Abstract: A coherent-modulation-imaging-based (CMI) algorithm has been employed for on-shot laser beam diagnostics in high-power laser facilities, where high-intensity short-pulsed lasers from terawatt to petawatt are designed to realize inertial confinement fusion (ICF). A single-shot intensity measurement is sufficient for wave-front reconstruction, both for the near-field and far-field at the same time. The iterative reconstruction process is computationally very efficient and was completed in dozens of seconds by the additional use of a GPU device to speed it up. The compact measurement unit—including a CCD and a piece of pre-characterized phase plate—makes it convenient for focal-spot intensity prediction in the target chamber. It can be placed almost anywhere in high-power laser facilities to achieve near-field wave-front diagnostics. The feasibility of the method has been demonstrated by conducting a series of experiments with diagnostic beams and seed pulses with deactivated amplifiers in our high-power laser system.